IMPLEMENTASI METODE WARD DAN PEPPARD DALAM PERENCANAAN SI/TI DI KANTOR ARSIP DAN PERPUSTAKAAN KOTA TASIKMALAYA - Melisa Winda Pertiwi (INTI Nusa Mandiri, 2020)
Development Strategy of Information Systems and Technology (SI/TI) in an organization of Government as well as a pemanfaata absolutely necessary to continue to improve the performance of employees in running business processes such as in the areas of coaching and Development Office of the archives and library of the town of Tasikmalaya don't have a business process excellence. Therefore, design kerangaka do it with in the planning SI/TI Using the method of analysis of the ward and Peppard has been in the form of results define strategy SI/TI The design of the framework of planning strategies SI/TI featuring the resulting Roadmap to future Application Portfolio. This future application can serve as a reference for the development of information systems are integrated to support the needs of the SI/TI Office of archives and library of the town of Tasikmalaya.